Determinants of Principal Job Satisfaction in West Java Province - Nurhasanah Pasaribu; Farida Jasfar; Lucy Warsindah; Syarifuddin Sulaiman (International Journal of Economics and Management Research, 2023)
In the world of education, the issue of job satisfaction and performance has become the main concern for academics. This study aims to investigate the impact of transformational leadership, education and training, and protean careers on job satisfaction. This research is a quantitative research to obtain and collect data and information that refers to the research problem. Data collection techniques based on field research were carried out in kindergarten private schools spread across regencies/cities in West Java Province. The population in this study were all Private Kindergarten (TK) Principals of 1,503 people. Sampling using random sampling and proportional sampling as many as 316 people. The analysis technique uses multiple linear regression analysis. The results showed that transformational leadership, and education and training variables had no significant effect on job satisfaction. The protean career variable has a significant effect on job satisfaction for school principals.